Differential adoption of plant protection technology by farmers of Kerala - a critical analysis - B.Meera (Department Of Agricultural Extension, College Of Agriculture, 1995)
Indian agriculture has undergone intensive farming with the introduction of high yielding varieties of crops. Adoption of improved technology and management practices for boosting up production of food grains have resulted in serious pest and disease complexes warranting intensive and extensive use of plant protection chemicals. A number of limitations and adverse side effects such as pest resistance to pesticides, pesticide residues, health hazards, environmental pollution and ecological imbalance have been identified recently.